Evaluation of vaginal microbiota in women admitted to the hospital for premature labour - Arena, Bruno; Daccò, Maria Diletta (Acta Biomedica Atenei Parmensis, 2021)
SUMMARY: Background and aim of the work: The aim of this study was to evaluate the vaginal microbiota of women admitted to the hospital for premature labour and to compare the flora of those who responded to the tocolytic treatment with the flora of those who did not respond to the treatment and delivered prematurely Materials: the hospital records of 245 women admitted to the division of Obstetrics and Gynaecology of ’Guglielmo da Saliceto’ Hospital in Piacenza for premature labour, between 24 completed weeks and 36 weeks plus 6 days of pregnancy, were reviewed and the results of vaginal swabs collected on admission were evaluated. Results : a vaginal dysbiosis, with reduction or absence of lactobacilli and presence of pathogenic microbial species, was found in all women admitted to the hospital for premature labour. Among them, 200 women (81,63%) responded to the tocolytic treatment while 45 women (18,36%) did not respond and delivered before 37 completed weeks. The four microbial species most prevalent in the vaginal flora were :Ureaplasma urealyticum, Streptococcus agalactiae, Candida albicans and Gardnerella vaginalis. When the characteristics of the vaginal flora of the two groups were compared, a more severe dysbiosis, with absence of lactobacilli and evidence of more than one pathogenic species, was found in 18% of women who responded to the tocolysis and in 71,4% of women who did not respond. The difference was statistically significant (p< 0,05, two-tailed test). Conclusions: vaginal dysbiosis was diagnosed in all women admitted to the hospital for premature labour . A more severe dysbiosis, with complete absence of lactobacilli and presence of two or more pathogenic microbial species, was in the majority of women who showed no response to the tocolytic treatment compared to women with minor degrees of alteration of the vaginal flora.